64-Channel Double-Layered Sieve Electrode with Increased Porosity for Improved Axon Regeneration and High Spatial Resolution - Jeong Jinwoo; Jung woo hyun; Kim Ockchul; Jun-Uk Chu; Inchan Youn; Keehoon Kim; Oh, Sang Rok; Jong Woong Park; KIM, JINSEOK (2016 6TH IEEE INTERNATIONAL CONFERENCE ON BIOMEDICAL ROBOTICS AND BIOMECHATRONICS (BIOROB), 2016)
Double-layered sieve-type neural electrode with high channel density is suggested for peripheral nerve interface. The neural electrode has double channel density due to its two separated metal layers including electrodes and distribution interconnects. Also it can be utilized to acquire and stimulate throughout the whole nerve cross-section. The measurement results of the electrochemical impedance confirm that the fabricated neural electrode has the neural signal recording feasibility. In-vivo implantation of the device is performed and functional recovery has been investigated. From the preliminary experimental results, new improved device design with higher porosity is suggested for next step.
Keywords: Sieve Electrode; null; Axon Regeneration; null; High Channel; null; Nerve Interface